Air conditioning and refrigeration - Miller, Rex, 1929-; Miller, Mark R. (New York : McGraw-Hill, 2012)
'Fully updated to cover the latest developments in air conditioning and refrigeration. Air Conditioning and Refrigeration, Second Edition, an introduction to the basic principles and practices of the air conditioning and refrigeration industry, contains all of the task-simplifying details needed for any project. Featuring more than 800 illustrations, the book provides step-by-step instructions for efficient, cost-effective, and current methods for choosing, installing, maintaining, troubleshooting, servicing, and repairing today's air conditioning and refrigeration equipment.New to this Edition: 16-page color insert Updated coverage of solenoids and valves EPA mandates for refrigerants and site safety Updated discussion of compressors Coverage of residential air conditioning units'--
'Fully updated to cover the latest developments in air conditioning and refrigeration, this is a must-have resource for beginners and seasoned AC professionals alike'--
Includes bibliographical references and index.
Keywords: Air conditioning; Refrigeration and refrigerating machinery